Interobserver variability in endometrial intraepithelial neoplasia - Supriya Sandeepa; Shwetha Ramu; Jayaprakash H T. (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Endometrial hyperplasia is a common disease and precursor of endometrial carcinoma. WHO hyperplasia classification system which is unreliable has confusing and overlapping criteria which prompted the development of a system based on Endometrial Intraepithelial Neoplasia (EIN).Objectives: (1) To review Endometrial Intraepithelial Neoplasia. (2) To reclassify WHO classification of endometrial hyperplasia into EIN and non-EIN category and to study the interobserver variability.Materials and Methods: In 102 patients diagnosed as WHO hyperplasia reclassification was done by 2 separate pathologists using EIN criteria 1) Glandular crowding. 2) Cytologic demarcation. 3) Size of the lesion should exceed 1mm. 4) Exclude benign processes 5) Exclude carcinoma. Inter observer variability was studied.Results: Out of 102 cases, 53 (51.96%) cases were earlier diagnosed as simple typical hyperplasia, 12 (11.76%) cases as complex typical hyperplasia, 21 (20.58%) cases as simple atypical hyperplasia and 16 (15.68%) cases as complex atypical hyperplasia. 26% were re-classified as EIN and 64% as non-EIN lesions by first pathologist. Second pathologist reclassified 28% as EIN and 62% as non-EIN lesions. Interobserver variability existed in only 2 cases of complex hyperplasia with atypia reclassified by second pathologist.Conclusion: EIN criteria has less interobserver variability than WHO classified hyperplasia system and can be easily applied to routine haematoxylin and eosin sections. EIN diagnosis prevents the progression to endometrial adenocarcinoma and helps in clinical management which is less intensive than for adenocarcinoma.